2012
DOI: 10.1371/journal.pone.0043331
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis of the Scorpion Centruroides noxius: New Toxin Families and Evolutionary Insights from an Ancestral Scorpion Species

Abstract: Scorpion venoms have been studied for decades, leading to the identification of hundreds of different toxins with medical and pharmacological implications. However, little emphasis has been given to the description of these arthropods from cellular and evolutionary perspectives. In this report, we describe a transcriptomic analysis of the Mexican scorpion Centruroides noxius Hoffmann, performed with a pyrosequencing platform. Three independent sequencing experiments were carried out, each including three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 55 publications
2
55
0
1
Order By: Relevance
“…The transcripts of NaTxs and KTxs are largely dominant, accounting for 36.9% of the total venom peptide transcripts of A. bicolor. This expression level is higher than those of Tityus stigmurus (14.8%), L. mucronatus (21.8%), and Isometrus maculatus (17.5%), but is lower than that of Centruroides noxius (54.6%), one of the most poisonous scorpions in the world [17,25,32]. It was shown that the sting of A. bicolor may cause pain, hyperemia, vomiting, swelling, restlessness and hypotension [73].…”
Section: Discussionmentioning
confidence: 99%
“…The transcripts of NaTxs and KTxs are largely dominant, accounting for 36.9% of the total venom peptide transcripts of A. bicolor. This expression level is higher than those of Tityus stigmurus (14.8%), L. mucronatus (21.8%), and Isometrus maculatus (17.5%), but is lower than that of Centruroides noxius (54.6%), one of the most poisonous scorpions in the world [17,25,32]. It was shown that the sting of A. bicolor may cause pain, hyperemia, vomiting, swelling, restlessness and hypotension [73].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the abovementioned reports, this study did not focus on the discovery of new toxins, but rather aimed at making a comprehensive multigene-based phylogenetic analysis of arthropods. C. noxius was the second Buthid species to be analyzed with this platform (Rendón-Anaya et al 2012). In this report, the transcriptomes of resting and active (milked) venom glands were compared and contrasted to a third cDNA library obtained from RNA extracted from the body after telson removal.…”
Section: Scorpion Transcriptome Analysis With High-throughput Technolmentioning
confidence: 99%
“…So far, we have some evidence that important toxin genes might be overexpressed right after the electric milking of the venom glands (Morgenstern et al 2011;Rendón-Anaya et al 2012), but, which other factors alter these toxin profiles? It has been suggested that the length and location of introns in toxin genes could alter to some extent their expression, as observed for K + channel toxins in M. martensii Zeng et al 2012).…”
Section: Future Directions For Scorpion Transcriptomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After, the cells grow in agar media. Finally, in isolating every clone in the library, the primary aim outlined above is obtained (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%